2010
DOI: 10.1097/sla.0b013e3181e61e4f
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Placement of Inferior Vena Cava Filters and Outcomes After Gastric Bypass Surgery

Abstract: Prophylactic IVC filters for gastric bypass surgery do not reduce the risk of pulmonary embolism and may lead to additional complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 29 publications
1
47
2
1
Order By: Relevance
“…20 For example, in a recent report of 6376 patients undergoing bariatric surgery, prophylactic IVC filters did not reduce postoperative VTE, but did appear to increase the risk of death and/or disability. 25 When IVC filters are necessary, retrievable filters are strongly recommended over permanent filters. ASH recommends that retrievable filters be removed as soon as the risk for PE has resolved and/or when anticoagulation can be safely resumed.…”
Section: Discussionmentioning
confidence: 99%
“…20 For example, in a recent report of 6376 patients undergoing bariatric surgery, prophylactic IVC filters did not reduce postoperative VTE, but did appear to increase the risk of death and/or disability. 25 When IVC filters are necessary, retrievable filters are strongly recommended over permanent filters. ASH recommends that retrievable filters be removed as soon as the risk for PE has resolved and/or when anticoagulation can be safely resumed.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, VTE-related deaths are the most important outcomes to evaluate in patients getting IVC filters. Birkmeyer et al [15] suggested a higher rate of fatal PE among the groups who had a prophylactic IVC filter placement. Unfortunately, causes of death were not consistently reported in included studies; only Overby et al [12] reported one out of three deaths related to PE.…”
Section: Mortality Related To Prophylactic Ivc Filter Placement Beformentioning
confidence: 99%
“…52 More direct, but lower-quality evidence comes from a large, prospective cohort study that used propensity scoring methods to compare VTE outcomes among bariatric surgery patients with and without IVC fi lters. 53 Before propensity adjustment, patients with IVC fi lters had higher rates of postoperative VTE and death or serious disability. Following propensity adjustment, the difference in postoperative VTE was no longer statistically signifi cant, but the risk of death or serious disability remained 2.5 times higher in the fi lter group.…”
Section: Ivc Filter Vs No Ivc Filtermentioning
confidence: 99%